PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PEMAHAMAN SISWA MENGENAI HAK DAN KEWAJIBAN SISWA SEKOLAH DASAR SEBAGAI WARGA NEGARA DI SDN 1 MANIKYANG - Rizkika Windasari; Ni Luh Nyoman Wina Wahini; Yuni Nuryanti; Putri Hidayah; Gusti Ngurah Bagus Tirtayadna; I Nyoman Sudiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of implementing the Problem-Based Learning (PBL) model on students’ understanding of rights and responsibilities as citizens at SDN 1 Manikyang. The research employed a quasi-experimental method using a pretest-posttest control group design. The sample consisted of two classes: the experimental class, which was taught using the PBL model, and the control class, which was taught using conventional teaching methods. Data were collected through pretest and posttest assessments and analyzed using descriptive and inferential statistical tests. The research findings indicate a significant improvement in the experimental class after implementing the PBL model. The average pretest score of the experimental class was 68.42, which increased to 79.19 in the posttest. In contrast, the control class had an average pretest score of 67.2, which slightly declined to 65.7 in the posttest. Statistical analysis confirmed that the difference in understanding improvement between the two classes was significant, demonstrating the effectiveness of the PBL model in enhancing students' comprehension of their rights and responsibilities as citizens. This improvement can be attributed to the active learning characteristics of the PBL model, which encourages students to think critically, engage in discussions, and seek solutions to real-life problems. Thus, problem-based learning can be an effective alternative instructional strategy for improving students’ understanding of Civic Education at the elementary school level.